First record of the genus Atrichobrunettia Satchell in Mexico, with the description of a new species (Diptera, Psychodidae, Psychodinae) - Ibáñez-Bernal, Sergio (Zootaxa, 2009)
Genus Atrichobrunettia Satchell is represented in the Americas by 14 described species, 13 from Brazil, and one from Costa Rica. Atrichobrunettia xalapaensis sp. nov. is described based on male and female characteristics and constitutes the first record of this genus in Mexico. This species belongs to subgenus A. (Polibrunettia) Bravo, but is easily distinguished from other described species of Polibrunettia by the form of the parameres and aedeagus in the male.